Radiation Therapy Strategies in Geriatric Patients: A Literature Review - Steven Octavianus; Soehartati A. Gondhowiardjo (Perhimpunan Dokter Spesialis Onkologi Radiasi Indonesia (PORI), 2021)
For humans, aging is defined as a universal biological process that manifests itself as a decrease in functional capacity and an increase in the risk of morbidity and mortality over time. Age is considered the single most significant risk factor for many chronic conditions including malignancies. Breast, lungs, prostate, colorectal, stomach, thyroid, pancreas, and ovarian cancers, as well as several types of leukemia, increase exponentially with age. Oncologists are often faced with difficulties when treat this population. Even though elderly and younger individuals seem to be able to get the same benefits result from a treatment, elderly are at greater risk of experiencing toxicity, serious side effects and death. A comprehensive multidisciplinary evaluation in elderly individuals with cancer can identify the risks and benefits of toxicity due to treatment plans including morbidity and mortality. Radiotherapy can be the solution in elderly with cancer, especially in patients at high risk for systemic therapy or surgery. Radiotherapy with modern techniques and fractionation adjustments (hypofractionation) can minimize the toxicity due to therapy and can be well tolerated by elderly individuals with cancer.